Microwave steam activation, an innovative pyrolysis approach to convert waste palm shell into highly microporous activated carbon - Yek, Peter Nai Yuh; Liew, Rock Keey; Osman, Mohammad Shahril; Lee, Chern Leing; Chuah, Joon Huang; Park, Young-Kwon; Lam, Su Shiung (Elsevier, 2019)
Microwave-steam activation (MSA), an innovative pyrolysis approach combining the use of microwave heating and steam activation, was investigated for its potential production of high grade activated carbon (AC) from waste palm shell (WPS) for methylene blue removal. MSA was performed via pyrolytic carbonization of WPS to produce biochar as the first step followed by steam activation of the biochar using microwave heating to form AC. Optimum yield and adsorption efficiency of methylene blue were obtained using response surface methodology involving several key process parameters. The resulting AC was characterized for its porous characteristics, surface morphology, proximate analysis and elemental compositions. MSA provided a high activation temperature above 500 °C with short process time of 15 min and rapid heating rate (≤150 °C/min). The results from optimization showed that one gram of AC produced from steam activation under 10 min of microwave heating at 550 °C can remove up to 38.5 mg of methylene blue. The AC showed a high and uniform surface porosity consisting high fixed carbon (73 wt%), micropore and BET surface area of 763.1 and 570.8 m 2 /g respectively, hence suggesting the great potential of MSA as a promising approach to produce high grade adsorbent for dye removal. © 2019 Elsevier Ltd